2021
DOI: 10.1037/com0000288
|View full text |Cite
|
Sign up to set email alerts
|

Visual discrimination of size and perception of the Delboeuf illusion in the domestic cat (Felis silvestris catus): A developmental disjunction?

Abstract: To date, no studies have examined the ontogeny of susceptibility to visual illusions in nonhuman mammals. Our previous study on the perception of the Delboeuf illusion by adult cats suggested they perceive this illusion, and that the visual processing involved in size judgment differs in the presence or absence of a misleading surround. We therefore asked whether weanling kittens are susceptible to the Delboeuf visual illusion, as adult cats are. Like the adults, kittens were presented with a series of 2-way f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…Finally, given the observed developmental patterns in human subjects it seems essential to investigated potential age effects also in nonhuman subjects. Some studies suggest developmental effects in mammals (Bánszegi et al, 2021) and birds (Rosa Salva et al, 2013) but unfortunately, the size of the current nonhuman primate sample does not allow for any meaningful analysis of this kind. Larger samples through multilab collaborations (ManyPrimates, 2019) and counterbalanced age compositions of the testing groups would allow for more controlled analyses of age effects in nonhuman subjects in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, given the observed developmental patterns in human subjects it seems essential to investigated potential age effects also in nonhuman subjects. Some studies suggest developmental effects in mammals (Bánszegi et al, 2021) and birds (Rosa Salva et al, 2013) but unfortunately, the size of the current nonhuman primate sample does not allow for any meaningful analysis of this kind. Larger samples through multilab collaborations (ManyPrimates, 2019) and counterbalanced age compositions of the testing groups would allow for more controlled analyses of age effects in nonhuman subjects in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Besides primates, other mammalian species have been shown to be susceptible to geometric illusions too—for example, in cats (Bánszegi et al, 2021; Szenczi et al, 2019), dogs (Byosiere et al, 2020; Keep et al, 2018), and horses (Cappellato et al, 2020).…”
mentioning
confidence: 99%
“…In our study, we tested the susceptibility of subjects belonging to 4 different ungulate species (i.e., guanacos, llamas, Skudde sheep and Damara goats) to the Müller-Lyer and Delboeuf illusions. Following the procedures previously used with other species (Bánszegi et al, 2021;Cappellato et al, 2020) we found that the study subjects perceived both the Müller-Lyer and the Delboeuf illusions in a similar way to humans, with no signi cant differences across species.…”
Section: Discussionmentioning
confidence: 57%
“…Comparisons with wild ungulates will thus be interesting to test the possible effect of environmental conditions on ungulate susceptibility to optical illusions. Similarly, future studies would benefit from the inclusion of a developmental approach, as susceptibility to illusions might change through age also in species other than humans (see e.g., Bánszegi et al 2021 , in cats). Finally, due to time constraints, we also did not include a control condition that is typically used when testing the Delboeuf illusion (Parrish and Beran 2014 ), in which the smaller food is on the smaller plate and the larger food on the larger plate, which allows excluding the possibility that subjects’ choices depend on the food-to-plate ratio.…”
Section: Discussionmentioning
confidence: 99%